Determining The Impact Of Green Distribution Activities On Perceived Business Performance: Kocaeli Logistics Enterprises Application - Ömer Ellibeş; Mualla Akçadağ (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
These days, it's crucial to practice environmental awareness, energy conservation, and resource preservation. Consumers today favor goods with high recycling rates and low environmental impact. Businesses who adopt social consciousness, are conscious of their social responsibilities, and work to satisfy customer expectations conduct their operations within the parameters of green marketing. Many operations, including green distribution activities, might benefit financially from reducing their use of fuel, packaging, and distribution routes.Enterprises can achieve performance efficiency through the selection of alternate distribution routes by logistics companies and the repurposing of spent packaging through reverse logistics. On the other side, in today's market, corporations use performance measurements to obtain a competitive advantage. Additionally, performance metrics help organizations guarantee customer happiness. With this in mind, the goal of this study is to ascertain how green distribution practices affect corporate success. It is also aimed to determine whether there is a relationship between green distribution activities and perceived business performance. To determine the population of the study, the list of enterprises operating in the logistics sector in Kocaeli was obtained from the Kocaeli Chamber of Commerce. In this sense, there are 102 companies on the list. All of these companies were interviewed face-to-face and a complete census sampling was carried out. Feedback was received from 86 of these companies. Regression and correlation analyses were carried out for this purpose utilizing the quantitative research approach. The survey method was used in the study to gather data. The study's findings led to the realization that green distribution procedures significantly and favorably impact company performance.